Teaching and Learning English Grammar: Opportunities and Challenges in ASEAN countries - Cando, Merigilda; Pelila, John Rey; Manogan, Keivy Xyrelle; Anagara, Ivy Joy; Pablito , Angel Mae (Papanda Publisher, 2025)
While substantial research has explored English grammar learning in East and South Asia, its classroom implementation in other Asian regions—particularly within ASEAN countries—remains underexamined. This study investigates the opportunities and challenges in implementing English grammar instruction across ASEAN countries. A systematic literature review was conducted using the ERIC database, focusing on peer-reviewed journal articles published between 2020 and 2024. Applying defined inclusion and exclusion criteria, 24 relevant articles covering five ASEAN countries (i.e., Indonesia, Malaysia, Philippines, Vietnam, and Thailand) were selected for analysis. Findings reveal that English grammar instruction enhances competence in the four macro language skills, improves grammatical accuracy, and increases learner confidence in academic and professional settings. However, challenges persist, including first language (L1) interference, limited student motivation, low confidence, and insufficient opportunities to use English in real-life contexts, often resulting in fear of criticism. To address these issues, the study emphasizes the importance of student-centered strategies, the integration of digital learning tools, and more opportunities for authentic communication. It is concluded that English grammar instruction positively impacts proficiency and confidence, but its full potential is constrained by persistent learner-related and instructional challenges. The study recommends checking for more recent studies from other ASEAN countries beyond the five reviewed, using additional databases, and encouraging classroom practices that foster real-world language use and regular student feedback.